Event-related (de)synchronization and potential in whole vs. part sensorimotor learning - Mariman, Juan J.; Bruna-Melo, Trinidad; Gutierrez-Rodriguez, Rosario; Maldonado, Pedro E.; Burgos, Pablo I. (Frontiers in Systems Neuroscience, 2023)
Background. There are different ways to learn a sensorimotor task. This research focuses on whole versus part learning in a complex video game that involves sensorimotor adaptations and skill learning. The primary aim of this research is to compare the changes in (1) event-related potentials (ERP) and (2) alpha and beta event-related desynchronization/synchronization (ERD(S)) of EEG between whole and part practice protocols. Methodology. 18 Healthy young participants practiced for five days a video game with distorted kinematic (advancing learning) and dynamic features (shooting learning) to test the ability to combine sensorimotor skill components learned modularly (part learning, 9 participants) or combined (whole learning, 9 participants). We examined ERP and ERD(S) in EEG channels in the baseline test (day 1) and the retention test (day 5), dissociating epochs with advancing or shooting. We focus the analysis on the main activity of ERP or ERD(S) in different time windows. Results. In the advancing epochs (distorted kinematic), both groups showed a decrease in time for ERP and an increase in beta ERD activity in central and posterior channels. In the shooting epochs (distorted dynamic), the Whole group showed a decrease in time for ERPs in anterior and central-posterior channels. Additionally, the shooting ERS in the Beta band decreases within sessions in central channels, particularly for the Part group. Conclusions. Neural correlates of kinematic and dynamic control (ERP and ERD(S)) were modulated by sensorimotor learning, which reflects the effect of the type of practice on the execution and the evaluation of the action. These results can be linked with our previous report (Burgos et al., 2018), where the simultaneous practice of kinematic and dynamic distortions takes advantage of the motor performance on retention tests, indicating a more automatic control for the whole practice group.